Aortic and Mitral Calcification Is Marker of Significant Carotid and Limb Atherosclerosis in Patients with First Acute Coronary Syndrome. (29th June 2015) - Sannino, Anna; Losi, Maria‐Angela; Giugliano, Giuseppe; Canciello, Grazia; Toscano, Evelina; Giamundo, Alessandra; Scudiero, Fernando; Brevetti, Linda; Scudiero, Laura; Prastaro, Maria; Perrino, Cinzia; Perrone‐Filardi, Pasquale; et al.
Abstract : Purpose: Atherosclerosis is a systemic disease and coronary artery disease is frequently associated with peripheral artery disease. As aortic and mitral valvular calcification (VC) share some etiopathogenetic mechanisms with atherosclerosis, we analyzed the risk profile and the echocardiographic characteristics of patients admitted for first acute coronary syndrome (ACS) to investigate whether the presence of VC could be a marker of asymptomatic hemodynamically significant peripheral atherosclerosis. Methods: A total of 151 patients admitted for ACS without previous history of cardiovascular disease were consecutively enrolled. The presence of VC was identified by echocardiography; a carotid stenosis ≥50% by ultrasound identified carotid artery disease (CarAD); an ankle–brachial index ≤0.9 or ≥1.4 identified lower extremity artery disease (LEAD). Significant peripheral atherosclerosis was defined by the presence of CarAD and/or LEAD. Results: Peripheral atherosclerosis was diagnosed in 82 (54.3%) patients; isolated CarAD in 24, isolated LEAD in 20, both diseases in 38 patients. VC was present in 103 (68.2%) patients. By multivariate analysis, age (OR = 1.059, 95% CI 1.007–1.113, P = 0.025), diabetes mellitus (OR = 5.068, 95% CI 1.480–17.351, P = 0.010), VC (OR = 7.422, 95% CI 2.421–22.880, P < 0.001), and multivessel CAD (OR = 3.317, 95% CI 1.281–8.586, P = 0.013) were the only independent predictors of having peripheral atherosclerosis. C‐statistic for VC was not inferior to that obtained by age (0.728, 95% CI 0.649–0.797 vs. 0.800, 95% CI 0.727–0.861, P = 0.101) and to that obtained by the combination of multivessel CAD with diabetes (0.750; 95% CI 0.673–0.817, P = 0.635), and, furthermore, it was higher than that obtained by diabetes alone (0.620, 95% CI 0.538–0.698, P = 0.036). Conclusion: Ruling out the presence of significant peripheral atherosclerosis should be routinely considered in patients with ACS showing VC at echocardiography.